2007
DOI: 10.1002/jbm.a.31197
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and osteogenic properties of silver‐containing hydroxyapatite coatings produced using a sol gel process

Abstract: Since bacterial infection is a rising complication following the wide use of implant, there is considerable attention on the effect of implant surface properties on bacterial adhesion. In this study, the effect of silver (Ag) doped hydroxyapatite (HA) coatings on initial antibacterial adhesion and osteoblast cell proliferation and differentiation was investigated. Using a sol-gel process, HA coatings doped with 1 wt % AgNO(3) (AgHA1.0) and 1.5 wt % Ag (AgHA1.5) were prepared. Coated surfaces were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(140 citation statements)
references
References 79 publications
3
128
0
Order By: Relevance
“…Pathogens found at infected oral implant sites, including S. mutans 90) , S. aureus 93,94) , S. oralis 43) , P. gingivalis and A. actinomycetemcomitans 84) were killed or significantly reduced upon contact with silver-implanted surfaces. All tested silver surfaces, such as hydroxyapatite (HA)-silver-surfaces 42,44,[46][47][48][49][50][51]91,161) or plasma sprayed silver-implanted HA 45,95) shared good antimicrobial activity.…”
Section: Silver-implanted Surfacesmentioning
confidence: 99%
“…Pathogens found at infected oral implant sites, including S. mutans 90) , S. aureus 93,94) , S. oralis 43) , P. gingivalis and A. actinomycetemcomitans 84) were killed or significantly reduced upon contact with silver-implanted surfaces. All tested silver surfaces, such as hydroxyapatite (HA)-silver-surfaces 42,44,[46][47][48][49][50][51]91,161) or plasma sprayed silver-implanted HA 45,95) shared good antimicrobial activity.…”
Section: Silver-implanted Surfacesmentioning
confidence: 99%
“…In the United States alone more than 4.4 million people have at least one internal fixation device and more than 1.3 million people have an artificial joint [55]. Bacterial infection induced by implant placement is a significant rising complication and is associated with considerable morbidity and costs [56]. Clinical practice has shown that systemic antibiotics are unable to provide effective treatment for implant-associated infections.…”
Section: Agecomentioning
confidence: 99%
“…Also, surgical techniques and device technology changed rapidly, often within the time frame of clinical studies, making the results diffi cult to interpret. [11][12][13][14][15][16] In addition, studies combined data from oncology, trauma, and adult reconstruction and included data from multiple anatomic locations. 2,3,9 These issues added to the complexity and inaccuracy of early outcome data, thereby making interpretation diffi cult.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have demonstrated no reduction in the bone ingrowth potential of standard hydroxyapatite. 12 Furthermore, nanotechnology has facilitated the manufacturing of more osteoconductive surface preparations that encourage more robust osseous ingrowth after implantation. 75 Similar to the proposed modifi cations to tumor endoprostheses already mentioned, porous prostheses with the capability to leach high local concentrations of antibiotics are also in design phase.…”
mentioning
confidence: 99%